GROCERY CONSUMER TYPOLOGIES ON ENVIRONMENTALLY SUSTAINABLE CONSUMPTION - Menezes, J.; Marques, C. (Fourth Multinational Enterprises and Sustainable Development International Conference (MESD’15), 2015)
The purpose of this paper is to characterize groups of customers based on their perceptions of value, satisfaction with retailers as well as on risk perceived in the seller-buyer relationship associated with their environmentally consumption practices. Most studies addressing the green consumption focuses on the product and in the buyer's decision about this product. An exchange perspective of the relationship customer-grocery recognizes the important role that both the seller and the shopper assume in their relationships, which influences consumer buying decision. However, studies on sustainable consumption in grocery stores are scarce justifying the need for greater knowledge about consumers’ behaviour on this phenomenon. As a result of cluster analysis, supported previously by a qualitative study in order to understand the risk perceived by the consumer is in the context of their grocery purchases, we obtained a consumers’ typology differing in their relational benefits, satisfaction and risks perceptions. Some suggestions are given to retailers and also recommendations about the need to closely consider their product offerings to ascertain what aspects contribute to the value considered by shoppers.